Explaining Trends in Adult Height in China: 1950 to 1990 - Minhee Chae; Tim Hatton; Xin Meng (Institute of Labor Economics (IZA), 2021)
This paper explores the changing trend of adult height in China for cohorts born in 1950-90. We use information on the household structure and local economic conditions during the individual's childhood to explain the trend. We find that during the 40-year period, the growth rate of adult height increased, with the most substantial increase occurring in the 1980s. One important contributing factor to the growth of adult height is the continued increase in government per capita spending on health and education. The impressive growth in the 1980s was mainly due to the introduction of market-oriented economic reforms, rather than the advent of the One-Child Policy. We find that the positive effect of economic reforms was larger for urban dwellers than for their rural counterparts and within the rural areas the benefit was far greater for men than for women.
Keywords: I15; I18; J13; O1; 330; height; China; economic reform